2006
DOI: 10.1021/ja061400a
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic, Structural, Mechanistic, and Computational Studies on Single-Site β-Diketiminate Tin(II) Initiators for the Polymerization of rac-Lactide

Abstract: A family of tin(II) complexes supported by beta-diketiminate ligands has been investigated as initiators for the polymerization of rac-lactide. Kinetic studies reveal a first-order dependence on [lactide], but with a significant induction period. Linear plots of M(n) versus conversion and [M](o)/[I](o) versus conversion, along with narrow molecular weight distributions (typically 1.07-1.10), are indicative of well-controlled, "living" polymerizations. Less sterically hindered derivatives promote faster propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
133
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(154 citation statements)
references
References 37 publications
13
133
2
Order By: Relevance
“…Many single site catalysts composed of various multivalent ligands were synthesized, and synthetic methods are known to synthesize PLA matters stereocontrolled from DL-lactide [52] (Figure 6). …”
Section: Stereo-controlled Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many single site catalysts composed of various multivalent ligands were synthesized, and synthetic methods are known to synthesize PLA matters stereocontrolled from DL-lactide [52] (Figure 6). …”
Section: Stereo-controlled Polymerizationmentioning
confidence: 99%
“…In Figure 6, the monomer combines weakly in the direction of trans of nitrogen donor of BDI ligand. The monomer and alkoxide ligand first exchange their sites by rotation, and then progress to TS1, the first transition state [52].…”
Section: Stereo-controlled Polymerizationmentioning
confidence: 99%
“…It is generally believed that ROP of cyclic esters operated by 'coordination-insertion' mechanism ( Figure 1). [49][50][51] Tolman group studied the kinetics of ROP of ɛ-caprolactone (CL) initiated by aluminum complexes, they suggested that ROP involved reversible binding of a cyclic ester to the metal (k 1 /k À1 ), attaching alkoxide to the activated carbonyl (k 2 /k À2 ) and generating a new propagating alkoxide (k 3 /k À3 ), The latter two steps were conceivably reversible. Although, the barrier for the ring-opening (k 3 ) would be lower than that of the ringclosing (k À3 ) and alkoxide deinsertion (k À2 ), k 3 was probably post-rate determining, so they simplified the mechanistic description to include only k 1 , k À1 , and k 2 .…”
Section: Mechanism For Ring-opening Polymerizations Of Cyclic Estermentioning
confidence: 99%
“…2,7,[9][10][11] Indeed, many studies have shown that the PLA microstructure can be controlled by the judicious choice of metal centre and ligand(s). However, despite much effort, including some computational studies, [12][13][14][15] challenges still remain to fully understand the interplay between metal, ligand, monomer and the growing polymer chain. There remains a high degree of serendipity in the stereochemical outcome of the polymerisation, with unpredictable tacticities achieved from metal-ligand combinations.…”
Section: Introductionmentioning
confidence: 99%